PERIODIZATION OF THE RESEARCH DEVELOPMENT ON FOREIGN CULTURAL AND EDUCATIONAL WORKERS IN UKRAINIAN PEDAGOGICAL COMPARATIVE SCIENCE - Kryvtsun, Neonila (Mountain School of Ukrainian Carpaty, 2023)
This article delves into the concept of periodization concerning the evolution of research on cultural-educational figures from other countries within the context of Ukrainian pedagogical comparativism. It sheds light on Ukrainian comparativists' emphasis on cultural-educational figures abroad, whose educational contributions and pedagogical legacies hold significance in Ukraine's historical-pedagogical field. In formulating a structured periodization, various overarching factors influencing this process were taken into account: socio-political elements (such as shifts in ideological perspectives, Ukraine's international relationships, the impact of the Russo-Ukrainian conflict, etc.); cultural-educational aspects (integration into the European educational sphere, heightened interest in foreign socio-cultural practices, the evolution of the information society, etc.); and the transformations within Ukrainian national humanitarianism and historical-pedagogical science, particularly in the realm of comparativism. The primary criterion for developing such a periodization scheme considered quantitative and qualitative changes that affected the historiographic process of accumulating knowledge on the discussed issue. This included the increase in the number of scholarly works (especially dissertations, professional articles, etc.), changes, and modifications in their substantive characteristics (methodology, introduction of new names into scholarly circulation, etc.). This study identifies three principal periods in the evolution of research on foreign figures within Ukrainian pedagogical comparativism. The initial phase, termed 'incipient' or 'initial,' spans from the 1970s to the 1980s, extending beyond the primary chronological boundaries of our research. The second period, characterized by a personalized direction in Ukrainian pedagogical comparativism, roughly spans from 1991/92 to 2004/05, denoted as the 'transitional post-Soviet' era. This phase marked notable shifts in research methodology, transitioning from a Soviet sociologized paradigm of analyzing educational-pedagogical processes to a nationally-oriented approach for study and interpretation. The third period, encompassing 2005/06 to 2025, is referred to as the 'Euro-oriented' and 'scientifically pluralistic' era. During this phase, active de-Sovietization and de-communization of national historical-pedagogical science facilitated the integration of Western European and American methodological approaches, concepts, research tools, and pedagogical ideologies. Ukraine's adoption of the Bologna Process in 2005 steered the country towards European educational standards, gradually distancing itself from Russian academic narratives due to the military aggression of the Russian Federation, ultimately leading to a clear rejection of these narratives.